Innovation at the faculty-level education through service learning - Mikelić Preradović, Nives; Boras, Damir; Lauc, Tomislava (2012)
The paper presents the service learning project titled DicDucFac (idea-leadership-product), that was planned and conducted by the team of information sciences students. It was planned as a workshop dealing with the application of modern social media (Facebook, YouTube, Gmail) for the purposes of self-promotion, free advertising via social networks and marketing own ideas and/or products in the virtual world. The workshop was organized for highly-skilled computer literate unemployed youth. These youth, as final beneficiaries, will be able to apply what they learned in this workshop to “the real world“, increasing their chances for employment and self- employment. The results of the project reveal that the basic, active-learning principles embodied in our teaching approach allow students to learn more effectively and gain essential life skills (from computer applications to teamwork) that can only be learned by doing. It also shows that our students received the essentials of professional ethics and citizenship through direct, personal engagement in professional activities and the life of the community.
Projekt MZOS
Projekt MZOS
ENG